Influence of cover crop mixtures on soil health in southeastern crop production systems - Anna M. Johnson (Wiley, 2021)
Abstract The restoration of soil health is a crucial step to maximize productivity in historically eroded soils of the southeastern United States. Cover crops have been known to improve soil health over time; therefore, studies were conducted from 2017 to 2019 in the Tennessee Valley (TVREC) and Wiregrass (WREC) Research and Extension Center regions of Alabama to examine the impact of cover crops on dynamic soil health indicators. Treatments including fallow, along with monocultures and combinations of cereal rye (Secale cereale L.), crimson clover (Trifolium incarnatum L.), and Daikon radish (Raphanus sativus L.) were arranged in a randomized complete block design in cotton (Gossypium hirsutum L.)–legume cash crop rotations. Soil health indicators included permanganate oxidizable C (POXC), total C (TC), water stable aggregates (WSA), and soil strength (area under the curve for cone index [AUCCI]). Cover crops did not increase WSA compared with fallow after 2 yr of treatment. At TVREC, POXC in the 10‐to‐15‐cm depth increased 60.6% under crimson clover compared with fallow. At TVREC, TC increased in the top 15 cm of soil after 2 yr of crimson clover, rye–clover, and rye–radish compared with fallow by 14.3, 11.6, and 15.2%, respectively. No differences in AUCCI occurred between treatments in 2018 at either location. In 2019, AUCCI at TVREC was higher under fallow and radish treatments compared with rye and rye–radish, whereas AUCCI at WREC in 2019 was higher under clover‐containing treatments compared with fallow and rye. Overall, some improvements in soil health indicators were observed after 2 yr of cover crop utilization, but long‐term cover crop use may be necessary to observe more consistent soil health changes.